High-performance network virtualisation for multilayer GMPLS networks. (8th April 2011) - Miyamura, T.; Masuda, A.; Shiomoto, K.
The recent trends in emerging network applications require more flexible network infrastructures. For this purpose, we consider the architecture and enabling technologies of high-performance network virtualisation using multilayer GMPLS networking technologies. The network virtualisation enables virtual network to utilise high-capacity bandwidth of optical network infrastructures without the provision of physical infrastructures. Furthermore, to improve robustness against network environmental changes such as failures and sudden traffic demand fluctuations, the network infrastructure provides virtual networks resource optimisation and on-demand resource distribution functions. One possible problem regarding virtualisation technologies lies in resource contention among multiple virtual networks sharing limited resources on the infrastructure. We thus propose a resource management model for efficient contention resolutions. We also present the design of a network virtualisation platform and the specification of interfaces to virtual network agents. We also developed prototype systems based on our system design and demonstrated the proposed high-performance lower-layer network virtualisation technologies in conjunction with commercially available routers and OXCs that support GMPLS protocols in our experimental network.